Distribution of Hydrogen-Producing Bacteria in Tibetan Hot Springs, China - Ma, Li; Wu, Geng; Yang, Jian; Huang, Liuqin; Phurbu, Dorji; Li, Wen-Jun; Jiang, Hongchen (Frontiers in Microbiology, 2021)
Abstract: Investigating the distribution of hydrogen-producing bacteria is of great significance to understanding of the source of biological hydrogen production in geothermal environments. Here, we explored the compositions of hydrogen-producing bacterial (HPB) populations in the sediments of hot springs from the Daggyai, Quzhuomu, Quseyongba and Moluojiang geothermal zones on the Tibetan Plateau, with the use of Illumina MiSeq high-throughput sequencing of 16S rRNA genes and hydA genes. In the present study, the hydA genes were successfully amplified from the hot springs with temperature of 46-87 °C. The hydA gene phylogenetic analysis showed that the top three phyla of the HPB populations were Bacteroidetes (14.48%), Spirochaetes (14.12%), and Thermotogae (10.45%), while Proteobacteria were absent in the top 10 of the HPB populations, although Proteobacteria were dominant in the 16S rRNA gene sequences. Canonical correspondence analysis results indicate the HPB community structure in the studied Tibetan hot springs was correlated with various environmental factors, such as temperature, pH, and elevation. The HPB community structure also showed a spatial distribution pattern, samples from the same area showed similar community structures. Furthermore, one hydrogen-producing bacterial isolate affiliated with Firmicutes was obtained and demonstrated the capacity of hydrogen production. These results are important for us to understand the distribution and function of hydrogen-producing bacteria in hot springs.